Development and validation of a prognostic score predicting recurrence in resected combined hepatocellular cholangiocarcinoma - Tian, Meng-Xin; Luo, Liu-Ping; Liu, Wei-Ren; Deng, Wei; Yin, Jia-Cheng; Jin, Lei; Jiang, Xi-Fei; Zhou, Yu-Fu; Qu, Wei-Feng; Tang, Zheng; Wang, Han; Tao, Chen-Yang; et al. (Cancer management and research, 2019)
To develop and validate a decision aid to help make individualized estimates of tumor recurrence for patients with resected combined hepatocellular cholangiocarcinoma (CHC). Risk factors of recurrence were identified in the derivation cohort of 208 patients who underwent liver resection between 1995 and 2014 at Zhongshan Hospital to develop a prediction score. The model was subsequently validated in an external cohort of 101 CHC patients using the C concordance statistic and net reclassification index (NRI). On multivariate analysis, five independent predictors associated with tumor recurrence were identified, including sex, γ-glutamyl transferase, macrovascular invasion, hilar lymphoid metastasis and adjuvant transcatheter arterial chemoembolization. The prediction score was constructed using these 5 variables, with scores ranging from 0 to 5. A patient with a score of 0 had a predicted 1- and 5-year recurrence risk of 11.1% and 22.2%, respectively. In the validation cohort, the NRIs of prediction score vs American Joint Committee on Cancer 7 TNM staging system at 1-year and 5-year were 0.185 (95% CI, 0.090-0.279, <0.001) and 0.425 (95% CI, 0.044-0.806, =0.03), respectively. Our developed and validated prediction score might be a simple and reliable method in postoperative CHC patients and help clinicians identify candidates who may benefit from future adjuvant therapies.